Magnesium Sulphate in Management of Severe Pre-eclampsia and Eclampsia - Dhakal, G; Subedi, M; Paudel, K (Journal of Nepal Health Research Council, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Pre-eclampsia and eclampsia (PE/E) are the second leading cause of maternal mortality in Nepal accounting for 21% of all maternal deaths and 30% of all facility based maternal deaths. For treatment of severe pre-eclampsia and eclampsia (SPE/E), WHO has identified magnesium sulphate (MgSO4) as the most effective and low cost medication. The objective of the study was to explore current situation of SPE/E management using MgSO4 in 10 health facilities of Mid Western Development Region. Methods: Descriptive and single group pre-test, post test study design was used for the study. Data were collected by reviewing records, taking interviews and through observation. Knowledge and skills of service provider was assessed and scored (0-100%) before and after the educational intervention. Results: One year records indicate that 0.5% SPE/E cases were found in Dang Sub Regional Hospital and Pyuthan District Hospital; 0.4% in Bheri Zonal Hospital; 0.9% in Mehelkuna PHCC and 0.5% in Rajapur PHCC. In most of the hospitals, these cases were managed with MgSO4. During pre-testing none of the health facility was able to get standard score (80%) but in post test, 50% health facilities were able to get 80% or higher score. Conclusions: Establishing national standard and providing one-time training is not sufficient, it requires refresher onsite training for propermanagement of SPE/E on time to improve maternal and neonatal health. <span style="font-size: 12.0pt; line-height: 115%; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Â Keywords: Magnesium Sulphate; Maternal and Newborn Care Quality Improvement Tool; Pre-eclampsia/Eclampsia; Severe Pre-eclampsia/Eclampsia.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>